If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(x) = -6x + -7 Multiply g * x gx = -6x + -7 Reorder the terms: gx = -7 + -6x Solving gx = -7 + -6x Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Divide each side by 'x'. g = -7x-1 + -6 Simplifying g = -7x-1 + -6 Reorder the terms: g = -6 + -7x-1
| -7(6x+2)=-266 | | 7x+2=5x+(-2) | | 6(-9x+5)=-240 | | 7(x)-2=26 | | -6(-6x-10)=276 | | -16+4x=5(x-1) | | 16n^2+8n+1= | | x^4-3x^3+4x^2-7x+15=0 | | 7-7n+3n=11-92 | | -6x-2=12 | | -9(6x-16)=468 | | 5(-10x-13)=-415 | | ln(x-1)=2.3 | | 6(9x+17)=426 | | 0=3t^2-2t | | x=y^2+125y+120 | | 7x+2*-2=6 | | 9(6x+5)=-441 | | 7y+6=13 | | X+5*3-10=80 | | 7(-7x-9)=-504 | | 8y+5=77 | | -30x^4/6x | | 9(-5x+2)=-342 | | 6x/18x^6 | | 6(7x+2)=222 | | 18x^6/6x | | 84=-26+x | | 2b-72+b-30=180 | | [(m-1)/(m-1)]0 | | 4(x+3)-2x+8= | | -5(7x+11)=-230 |